A potter's book - Leach, Bernard (London Faber, 1955)
slipware, kiln, saggars, china clay, silica, feldspar, celadons, studio potter, Shoji Hamada, Michael Cardew, fireclay, quartz, Ming porcelain, ball clay, Sung dynasty, Japan, tenmoku, iron oxide, fluxing agents, sgraffito
1. Towards a Standard
2. Raku - English Slipware - Stoneware - Porcelain
3. Clays
4. The Making of Clay Shapes
5. Decoration
6. Pigments and Glazes
7. Kilns
8. The Workshop
- Includes bibliographical references and index
- Includes plates in black and white and some in colour
Keywords: Pottery